PROBLEMS OF INCREASING INVESTMENT ACTIVITY IN THE CONTEXT OF GLOBALIZATION (International journal of artificial intelligence, 2024)
This article examines the problems of increasing investment activity in the context of globalization. In addition, the necessary conclusions and recommendations are presented on increasing investment attractiveness in the context of globalization.